Metformin Promotes the Protection of Mice Infected With Plasmodium yoelii Independently of γδ T Cell Expansion - Miyakoda, Mana; Bayarsaikhan, Ganchimeg; Kimura, Daisuke; Akbari, Masoud; Udono, Heiichiro; Yui, Katsuyuki (Frontiers in Immunology, 2018)
Adaptive immune responses are critical for protection against infection with Plasmodium parasites. The metabolic state dramatically changes in T cells during activation and the memory phase. Recent findings suggest that metformin, a medication for treating type-II diabetes, enhances T-cell immune responses by modulating lymphocyte metabolism. In this study, we investigated whether metformin could enhance anti-malaria immunity. Mice were infected with Plasmodium yoelii and administered metformin. Levels of parasitemia were reduced in treated mice compared with those in untreated mice, starting at 2 weeks post-infection. The number of γδ T cells dramatically increased in the spleens of treated mice compared with that in untreated mice during the later phase of infection, while that of αβ T cells did not. The proportions of Vγ1+ and Vγ2+ γδ T cells increased, suggesting that activated cells were selectively expanded. However, these γδ T cells expressed inhibitory receptors and had severe defects in cytokine production, suggesting that they were in a state of exhaustion. Metformin was unable to rescue the cells from exhaustion at this stage. Depletion of γδ T cells with antibody treatment did not affect the reduction of parasitemia in metformin-treated mice, suggesting that the effect of metformin on the reduction of parasitemia was independent of γδ T cells.